Karekteristik Hidroksiapatit (HA) Dari Limbah Tulang Sapi dengan Metode Mekanik-Termal - Ikhsan - -; Gunawarman - -; Yuli Yetri - (Jurnal Ilmiah Poli Rekayasa, 2018)
The availability of bovine bone waste is very abundant and has not been utilized optimally as raw material for the manufacture of Hydroxyapatit (HA).HA is widely used in the field of orthopedics and dentistry, because it is biocompatible and bioactive, bovine bone wastes are synthesized by thermal-mechanical methods to obtain HA. The first stage of bovine bone preparation is done to obtain HA from bovine bone waste by mechanical collision to obtain bone meal smooth. The second stage of calcination at a temperature of 800oC. The results of microstructural observation with SEM obtained granules obtained almost evenly smoothness with average size 42.25 μm in span (irregular spherical (30.29-136.4μm) and chemical composition with XRF obtained by Ca / P ratio of 1.61, close to the optimal value of HA of 1.67.